Community-Based Cultural Heritage Preservation: Study of Historical Relics in Palu City, Central Sulawesi - Ismail Ismail*; Mutawakkil Mutawakkil; Priyatna Prasetyawati (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Palu City has a lot of Cultural Conservation, but none has been designated as Cultural Conservation. Reserve Culture in Palu City many have experienced it damage and neglected because it did not receive serious attention from the government and the local community. Study this aims to determine the preservation of Cultural Heritage in Palu City. This study uses a qualitative approach which characteristic descriptive through determining clusters and identifying community participation in Cultural Heritage in Palu City. The results of this study prove three things, namely (1) Cultural Heritage Preservation in Palu City has not been carried out in accordance with Law Number 11 of 2010 because there is no PERDA yet. (2) The efforts of the Palu City Government in preserving Cultural Conservation have not been maximized, so that many Cultural Conservation have been damaged. (3) Community participation in Cultural Conservation in Palu City is very minimal. This is caused by a lack of knowledge about the importance of cultural assets to be preserved.